2006
DOI: 10.1007/s00125-006-0335-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment with interleukin-1β induces insulin resistance in murine and human adipocytes

Abstract: Aims/hypothesis Adipose tissue inflammation has recently been implicated in the pathogenesis of insulin resistance and is probably linked to high local levels of cytokines. IL1B, a proinflammatory cytokine, may participate in this alteration. Materials and methods We evaluated the chronic effect (1-10 days) of IL1B (0.1-20 ng/ml) on insulin signalling in differentiating 3T3-F442A and differentiated 3T3-L1 murine adipocytes and in human adipocytes. We also assessed expression of the gene encoding IL1B in adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
184
3
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(194 citation statements)
references
References 49 publications
5
184
3
2
Order By: Relevance
“…Furthermore, long-term IL-1a stimulation of 3T3-L1 adipocytes induced expression of suppressor of cytokine signaling-1 and -3 (He et al 2006), which are well-established inhibitors of insulin signal transduction (Fasshauer et al 2004). In addition, IL-1b dramatically decreased the production of the insulinsensitizing adipokine adiponectin in 3T3-L1 adipocytes and in human primary fat cells (Lagathu et al 2006). Consistent with these findings, Thomas and co-workers have shown that IL-1 receptor-deficient non-obese diabetic mice were partially protected from the development of T2DM (Thomas et al 2004).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Furthermore, long-term IL-1a stimulation of 3T3-L1 adipocytes induced expression of suppressor of cytokine signaling-1 and -3 (He et al 2006), which are well-established inhibitors of insulin signal transduction (Fasshauer et al 2004). In addition, IL-1b dramatically decreased the production of the insulinsensitizing adipokine adiponectin in 3T3-L1 adipocytes and in human primary fat cells (Lagathu et al 2006). Consistent with these findings, Thomas and co-workers have shown that IL-1 receptor-deficient non-obese diabetic mice were partially protected from the development of T2DM (Thomas et al 2004).…”
Section: Introductionsupporting
confidence: 52%
“…Biologically active proteins secreted from adipose tissue, so-called adipokines, are suggested to link obesity with associated disorders including insulin resistance, type II diabetes mellitus (T2DM), and cardiovascular diseases (Fasshauer & Paschke 2003). Recently, interleukin (IL)-1b has been characterized as a novel fat-secreted adipokine with insulin resistance-inducing and proinflammatory properties besides tumor necrosis factor (TNF)-a and IL-6 (Lagathu et al 2006, Barksby et al 2007, Jager et al 2007. Thus, chronic IL-1b treatment impaired insulininduced glucose transporter (Glut)-4 expression and markedly inhibited its translocation to the plasma membrane through downregulation of insulin receptor substrate-1 (Jager et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of NLRP3 activity in adipose tissue macrophages (ATMs) during diet-induced obesity may mediate insulin resistance in adipocytes via IL-1 secretion [39] . Secreted IL-1 is reported to disrupt the insulin signaling pathway, reduce the expression of insulin receptor substrate 1 (IRS1), and lead to decreased insulinmediated glucose uptake resulting in insulin resistance [89,90] . Secreted IL-1 can also lead to its transcriptional autoregulation by a positive feedback loop via NF-κB pathways [91] , leading to amplification of the priming signal.…”
Section: Obesity-linked Diseasementioning
confidence: 99%
“…[1][2][3][4] The mechanisms through which pro-inflammatory cytokines, like tumor necrosis factor-a, interleukin-6 (IL-6) and IL-1b interact with cellular insulin signal transduction cascades have been described in the last years. [5][6][7][8][9] Lactoferrin is a pleiotropic glycoprotein (80 kDa) and a prominent component of the first line of mammalian host defense, acting on specific lactoferrin receptors that exist in a variety of cells, like monocytes, lymphocytes, adipocytes, hepatocytes and endothelial cells. 10 Lactoferrin expression is upregulated in response to inflammatory stimuli.…”
Section: Introductionmentioning
confidence: 99%